Pengaruh Kualitas Pelayanan Perawat Dan Fasilitas Paramedis Terhadap Kepuasan Pasien : (Studi pada Ruang Rawat Inap Badan Layanan Umum Daerah Rumah Sakit Umum Kota Banjar) - Wadi Wadi; Ading Rahman Sukmara; Ferey Herman (Pajak dan Manajemen Keuangan, 2024)
The problems faced in this study include (1) How does the quality of nurse services affect patient satisfaction in the Inpatient Room of the Regional Public Service Agency of the Banjar City General Hospital? (2) How do paramedic facilities affect patient satisfaction in the Inpatient Room of the Regional Public Service Agency of Banjar City General Hospital? (3) How does the quality of nurse services and paramedic facilities affect patient satisfaction in the Inpatient Room of the Regional Public Service Agency of Banjar City General Hospital? This study aims to study, know, and analyze (1) The effect of nurse service quality on patient satisfaction in the Inpatient Room of the Regional Public Service Agency of Banjar City General Hospital. (2) The effect of paramedic facilities on patient satisfaction in the Inpatient Room of the Regional Public Service Agency of Banjar City General Hospital. (3) The effect of the quality of nurse services and paramedic facilities on patient satisfaction in the Inpatient Room of the Regional Public Service Agency of the Banjar City General Hospital.The method used in this study is an explanatory survey, while the data analysis techniques, namely validity tests, reliability tests, descriptive statistics, Inferential Statistical Analysis with Multiple Regression. The results of the study inform that (1) The quality of nurse services has a positive effect on patient satisfaction in the Inpatient Room of the Regional Public Service Agency of the Banjar City General Hospital. This means that if the quality of service is improved, then patient satisfaction in the Inpatient Room of the Regional Public Service Agency of the Banjar City General Hospital will also increase. (2) Paramedic facilities have a positive effect on patient satisfaction in the Inpatient Room of the Regional Public Service Agency of the Banjar City General Hospital. This means that if paramedic facilities are improved, patient satisfaction in the Inpatient Room of the Regional Public Service Agency of the Banjar City General Hospital will also increase. (3) The quality of nurse services and paramedic facilities has a positive effect on patient satisfaction in the Inpatient Room of the Regional Public Service Agency of Banjar City General Hospital. This means that if the quality of nurse services and paramedic facilities is improved, patient satisfaction in the Inpatient Room of the Regional Public Service Agency of the Banjar City General Hospital will also increase.